Davallia mariesii Moore Improves FcεRI-Mediated Allergic Responses in the Rat Basophilic Leukemia Mast Cell Line RBL-2H3 and Passive Cutaneous Anaphylaxis in Mice - Do, Hyun Ju; Oh, Tae Woo; Yang, Ju Hye; Park, Kwang Il; Ma, Jin Yeul (Mediators of Inflammation, 2017)
Davallia mariesii Moore (Drynaria rhizome extract (DRE)) is widely known for its efficacy in treating inflammation, arteriosclerosis, and bone injuries. This study evaluated whether treatment with DRE inhibited FcɛRI-mediated allergic responses in the RBL-2H3 mast cells and investigated the early- and late-phase mechanisms by which DRE exerts its antiallergic effects. IgE anti-DNP/DNP-HSA-sensitized RBL-2H3 mast cells were tested for cytotoxicity to DRE, followed by the assessment of β-hexosaminidase release. We measured the amounts of inflammatory mediators (e.g., histamine, PGD2, TNF-α, IL-4, and IL-6) and examined the expression of genes involved in arachidonate and FcεRI signaling pathways. In addition, we confirmed the antiallergic effects of DRE on passive cutaneous anaphylaxis (PCA) in mice. DRE inhibited RBL-2H3 mast cell degranulation and production of allergic mediators in them. In early allergic responses, DRE reduced expression of FcεRI signaling-related genes (e.g., Syk, Lyn, and Fyn) and extracellular signal-regulated kinase phosphorylation in mast cells. In late allergic responses, DRE reduced PGD2 release and COX-2 expression and cPLA2 phosphorylation in FcɛRI-mediated mast cells. Lastly, 250–500 mg/kg DRE significantly attenuated the IgE-induced PCA reaction in mice. These findings provide novel information on the molecular mechanisms underlying the antiallergic effects of DRE in FcɛRI-mediated allergic responses.